Study protocol to investigate biomolecular muscle profile as predictors of long-term urinary incontinence in women with gestational diabetes mellitus - Rudge, Marilza V. C. [UNESP]; Souza, Fátima P. [UNESP]; Abbade, Joelcio F. [UNESP]; Hallur, Raghavendra L. S. [UNESP]; Marcondes, João Paulo C. [UNESP]; Piculo, Fernanda [UNESP]; Marini, Gabriela [UNESP]; Vesentini, Giovana [UNESP]; Thabane, Lehana; Witkin, Steven S.; Calderon, Iracema M. P. [UNESP]; Barbosa, Angélica M. P. [UNESP]; et al. (Springer Nature, 2020)
Background: Pelvic floor muscles (PFM) and rectus abdominis muscles (RAM) of pregnant diabetic rats exhibit atrophy, co-localization of fast and slow fibers and an increased collagen type I/III ratio. However, the role of similar PFM or RAM hyperglycemic-related myopathy in women with gestational diabetes mellitus (GDM) remains poorly investigated. This study aims to assess the frequency of pelvic floor muscle disorders and pregnancy-specific urinary incontinence (PS-UI) 12 months after the Cesarean (C) section in women with GDM. Specifically, differences in PFM/RAM hyperglycemic myopathy will be evaluated. Methods: The Diamater is an ongoing cohort study of four groups of 59 pregnant women each from the Perinatal Diabetes Research Centre (PDRC), Botucatu Medical School (FMB)-UNESP (São Paulo State University), Brazil. Diagnosis of GDM and PS-UI will be made at 24-26 weeks, with a follow-up at 34-38 weeks of gestation. Inclusion in the study will occur at the time of C-section, and patients will be followed at 24-48 h, 6 weeks and 6 and 12 months postpartum. Study groups will be classified as (1) GDM plus PS-UI; (2) GDM without PS-UI; (3) Non-GDM plus PS-UI; and (4) Non-GDM without PS-UI. We will analyze relationships between GDM, PS-UI and hyperglycemic myopathy at 12 months after C-section. The mediator variables to be evaluated include digital palpation, vaginal squeeze pressure, 3D pelvic floor ultrasound, and 3D RAM ultrasound. RAM samples obtained during C-section will be analyzed for ex-vivo contractility, morphological, molecular and OMICS profiles to further characterize the hyperglycemic myopathy. Additional variables to be evaluated include maternal age, socioeconomic status, educational level, ethnicity, body mass index, weight gain during pregnancy, quality of glycemic control and insulin therapy. Discussion: To our knowledge, this will be the first study to provide data on the prevalence of PS-UI and RAM and PFM physical and biomolecular muscle profiles after C-section in mothers with GDM. The longitudinal design allows for the assessment of cause-effect relationships between GDM, PS-UI, and PFMs and RAMs myopathy. The findings may reveal previously undetermined consequences of GDM.
Keywords: Collagen; Electromyography; Gestational diabetes mellitus; Hyperglycemic myopathy; Pelvic floor muscles; Proteomics; Rectus abdominis muscles; Transmission electron microscopy; Urinary incontinence